Avaliação formativa em um contexto de educação corporativa : uma narrativa com enfoque pedagógico - Casaletti, Bárbara Burgardt (2017)
This thesis was elaborated in the research line Education, Policies and Practices in Education of the Program of Post-Graduation in Education of PUCRS and investigated how the evaluation of training and improvement actions in a corporate education context is being carried out. Its construction is inspired by the Resolutions of the National Council of Justice – CNJ – and the Superior Council of Labor Justice - CSJT, which deal with the national policy of training and perfecting the servants of the Judiciary, as well as the national policy of education for servers of Labor Justice of first and second degree. In the process of data collection, the interview was used, which, according to Severino (2013), provides an interaction between the researcher and his interlocutors. The respondents were chosen intentionally within the universe investigated and the approach of the interviews (semi-structured) and the other data collected were submitted to discursive textual analysis, according to terms proposed by Moraes and Galliazzi (2011), the following categories being previously defined were: 1ª) assessment and reaction; 2ª) learning assessment; 3ª) application assessment; 4ª) outcome assessment. Those categories were chosen according to the content of the aforementioned Resolutions, where it is expected that “training and improvement actions will be evaluated, whenever possible, by the organs of the judiciary, to guide new decision-making and the specificity of the Formative action in four dimensions: reaction, learning, application and outcome” (Resolution CNJ nº 192/2014 and Resolution CSJT nº 159/2015). In addition, the studies of Kirkpatrick and Kirkpatrick (2010a, 2010b) were also considered. The narrative as method was assumed, in the terms proposed by Clandinin and Connelly (2000), where the temporality and the stories lived and narrated are considered.